Ali delo v rudniku vpliva na vidne funkcije - Prelesnik, Uroš (Zdravniški vestnik, 2002)
Background. In the article we described the condition of miners vision before they started working in the mine and after twenty years of continuous work in the pit. We presumed that working in the dark and uncomfortable conditions distort the vision. We found no similar analysis in the literature that was available to us. So we started with the analysis in our institution. As ophthalmologist and specialist of occupational medicine we daily came across miners questions and findings about the distortion of their vision after working in the pit for many years. Criteria of visual functions for the minersare: visual acuity of the better eye should be at least 0.7 and at least0.5 of the worse one, without correction. He has to have normal binocularvision and normal night vision. Normal colour vision is not obligatory for the miners which allows the dicromats (colour blind people) to work, too. Methods. We treated 50 miners who started to work in the mine in theyears 1977-1979 and have spent their whole working period in the mine. We had a lot of problems choosing the miners because of fluctuation (superannuations, leaving Slovenia), so they did not come to ophthalmologist at the end of their working period. In our dispensary of occupational medicinethey were last treated the last year before retiring, while the ophthalmologist examined them in the years 1997-1999. In our dispensary of occupational medicine they were examined by the orthoreter or R22 where monocular vision, binocular vision, depth vision and colour vision were checked. The ophthalmologist examined the vision without and with correction, measured the eye pressure, performed the examination on the slitlamp and checked the eye background. (Abstract truncated at 2000 characters).
Keywords: diagnostika; Mining; motnje; Occupational exposure; Oftalmoskopija; Ophthalmoscopy; Poklicna izpostavljenost; rudarji; Rudarstvo; vid; Vid, motnje; Vid, testi; Vision disorders; Vision tests